Fractional Cauchy problems on compact manifolds. Issue 2 (3rd March 2016) - D'Ovidio, Mirko; Nane, Erkan
ABSTRACT: We investigate anomalous diffusion on compact Riemannian manifolds, modeled by time-changed Brownian motions. These stochastic processes are governed by equations involving the Laplace–Beltrami operator and a time-fractional derivative of order β ∈ (0, 1). We also consider time dependent random fields that can be viewed as random fields on randomly varying manifolds.